(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Vitamin D is important for all age groups, especially women in menopause. In order to improve the health status of women in their post-menopausal stage, earlier identification of the risk population and prevention of the diseases in perimenopausal stage becomes indispensable. Due to the sharp increase in the morbidity status of elderly women, a study on the vitamin D status in perimenopausal women is essentially important, as an early identification and focus on promoting health, may reduce the disease in later life. The study was conducted in department of Biochemistry, Melmaruvathur Adhiparasakthi Institute of Medical Science and Research. This is descriptive study. Totally 72 perimenopausal was involved in this study and divided into two groups, each group consist of 36 women’s. Vitamin D levels were significantly decreased in Hypovitaminosis D perimenuopausal women when compared with sufficient Vitamin D perimenuopausal women. In the present study we conclude that the Urgent measures needed should also include the assessment of vitamin D status in the population especially in females. It is reasonable for women to have 25(OH)D concentration measured at least once a year.